Scheduling smart home appliances using mixed integer linear programming - Kin Cheong Sou; Weimer, J.; Sandberg, H.; Johansson, K. H. (2011 50th IEEE Conference on Decision and Control and European Control Conference, 2011)
This paper considers the minimum electricity cost scheduling problem of smart home appliances. Operation characteristics, such as expected duration and peak power consumption of the smart appliances, can be adjusted through a power profile signal. The optimal power profile signal minimizes cost, while satisfying technical operation constraints and consumer preferences. Constraints such as enforcing uninterruptible and sequential operations are modeled in the proposed framework using mixed integer linear programming (MILP). Several realistic scenarios based on actual spot price are considered, and the numerical results provide insight into tariff design. Computational issues and extensions of the proposed scheduling framework are also discussed.